MOLECULAR AND IMMUNOLOGICAL DETECTION OF GLIOTOXIN GENES IN ASPERGILLUS FUMIGATUS ISOLATED FROM PATIENTS WITH INVASIVE PULMONARY ASPERGILLOSIS - Hussein, Anmar S.; Mohammed, Sanaa H.; Mohammed, Bari L. (Eastern Ukrainian Medical Journal, 2025)
Introduction: Aspergillus fumigatus, a filamentous fungus, is a leading cause of invasive pulmonary aspergillosis (IPA), a severe condition predominantly affecting immunocompromised patients. Gliotoxin, a secondary metabolite crucial to A. fumigatus virulence, is produced through a biosynthetic pathway regulated by several genes, including GliP, GliA, and GliJ. It plays a significant role in its pathogenicity, affecting host immune responses and contributing to disease progression. This study aimed to molecularly and immunologically detect gliotoxin-related genes in A. fumigatus isolates from IPA patients. Methods: Forty patients diagnosed with IPA were recruited, and sputum and plasma samples were collected to identify fungal isolates and assess plasma interleukin-17 (IL-17) levels. Molecular detection of A. fumigatus involved extracting genomic DNA from isolates, followed by polymerase chain reaction (PCR) using primers for the gliotoxin biosynthetic genes GliP, GliZ, and GliA. Additionally, plasma IL-17 levels were measured in IPA patients to assess their immunological response and gliotoxin production was confirmed using thin-layer chromatography. Results: Of the 40 isolates, 20 were confirmed to be A. fumigatus. PCR analysis revealed that 85% of these isolates harbored the GliP gene, while 75% carried the GliZ gene. Also, 40% of the isolates demonstrated gliotoxin production. The IL-17 levels in patients with IPA (1660.10±103.65 pg/mL) were significantly higher compared to the control group (807.92±101.51 pg/mL). The elevated IL-17 levels observed in IPA patients underscores the role of this cytokine in the immune response against A. fumigatus. The detection of gliotoxin-producing isolates varied, with genetic and environmental factors influencing gliotoxin biosynthesis. Isolates lacking either GliP or GliZ failed to produce gliotoxin, while some isolates with both genes exhibited reduced toxin production, likely due to regulatory influences. Conclusion: The study found that a combination of molecular and immunological methods offers a promising diagnostic tool for detecting IPA and understanding A. fumigatus virulence. Future research could enhance diagnostic tools' sensitivity and specificity, apply them in clinical settings, and develop non-invasive methods like biomarkers for improved patient outcomes.